2015
DOI: 10.1007/s11356-015-4428-4
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of fatty acid harvesting by novel carbon-based adsorbent

Abstract: In this study, separation and concentration of fatty acids (FA) from the synthetic food processing wastewater containing low concentration of FA (250 mg/L) were investigated using expanded graphite (EG) as a novel adsorbent at different temperatures (298~318 K). The adsorption results were further analyzed to verify adsorption mechanisms and thermodynamics of FA onto EG. Results show that the adsorption of FA onto EG was explained well by the Langmuir model with the maximum adsorption capacity up to 8.01 g FA/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The experimental equilibrium data of Pb 2+ and Ni 2+ adsorption onto the prepared MONPs-EG in single and binary metals systems were characterized using Langmuir and Freundlich isotherms [28][29][30]; their mathematical expressions are given by the following Equations (2) and 3, respectively.…”
Section: Adsorption Isothermsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental equilibrium data of Pb 2+ and Ni 2+ adsorption onto the prepared MONPs-EG in single and binary metals systems were characterized using Langmuir and Freundlich isotherms [28][29][30]; their mathematical expressions are given by the following Equations (2) and 3, respectively.…”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…The higher magnitude of ∆S 0 obtained in the Pb 2+ system signified that it had a better affinity toward and was more stable on the MONPs-EG compared to Ni 2+ . Furthermore, negative values of ∆G 0 at all investigated temperatures indicated that the adsorptions of both metal ions onto the prepared MONPs-EG were thermodynamically favorable and spontaneous in nature [28,50]. Humic acids (HA) are the major components of dissolved organic matter in natural surface water.…”
Section: Thermodynamic Studymentioning
confidence: 99%
See 1 more Smart Citation